Asymmetric Henry Reactions of Aldehydes Using Chiral Biaryl-Based Bis(thiourea) Organocatalysts - Nakayama, Yuki; Hidaka, Yusaku; Ito, Katsuji (Synlett, 2013)
Biaryl-based bis(thiourea) was found to be an efficient organocatalyst for the asymmetric Henry reaction. High enantioselectivity of up to 93% ee was obtained for the reaction of nitromethane with aryl aldehydes when the combination of N,O-bis(trimethylsilyl)trifluoroacetoamide (BSTFA) with a catalytic amount of potassium acetate was used as the base.
Keywords: asymmetric catalysis; bis(thiourea); Henry reaction; nucleophilic addition; enantioselectivity